2004
DOI: 10.1111/j.1442-200x.2004.01909.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic role of 99mTc hexamethyl‐propyleneamine oxime brain single photon emission computed tomography in Sydenham's chorea

Abstract: It is suggested that brain SPECT can contribute to the diagnosis of SC as an objective tool. Resolving of the hyperperfusion at the recovery phase provides further support for the diagnosis of SC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In study of seventeen patients with Sydenham chorea, 99m Tc HMPAO-SPECT performed 0 to 3 weeks from symptom onset demonstrated hyperperfusion in the basal ganglia and thalamus in 94.1% of patients and was normal in one patient. Follow-up 99m T HMPAO-SPECT performed 6–12 months later showed reduction in perfusion compared to the acute phase and perfusion of the basal ganglia and thalamus was similar to controls [60]. Although the data in Sydenham chorea is somewhat inconsistent in the acute phase because some studies indicate hyperperfusion in the basal ganglia and others demonstrate hypoperfusion, all follow-up studies after the resolution of chorea demonstrate normal perfusion.…”
Section: Single-photon Emission Computed Tomography (Spect)mentioning
confidence: 99%
“…In study of seventeen patients with Sydenham chorea, 99m Tc HMPAO-SPECT performed 0 to 3 weeks from symptom onset demonstrated hyperperfusion in the basal ganglia and thalamus in 94.1% of patients and was normal in one patient. Follow-up 99m T HMPAO-SPECT performed 6–12 months later showed reduction in perfusion compared to the acute phase and perfusion of the basal ganglia and thalamus was similar to controls [60]. Although the data in Sydenham chorea is somewhat inconsistent in the acute phase because some studies indicate hyperperfusion in the basal ganglia and others demonstrate hypoperfusion, all follow-up studies after the resolution of chorea demonstrate normal perfusion.…”
Section: Single-photon Emission Computed Tomography (Spect)mentioning
confidence: 99%
“…Cognitive function in SC patients has not been well studied 1 . Some authors have described impairment of learning capacity, lower intellectual level, changes in response inhibition, divided attention, and planning ability tasks 2,3 . In most studies it is suggested that, there is an evidence of basal ganglia dysfunction which can be showed by morphologic and functional neuroimaging techniques 4 .…”
mentioning
confidence: 99%
“…56 Single-photon emission computed tomography (SPECT) studies have shown hyper-or hypometabolism in the basal ganglia during acute SC. 50,57 Although these changes are usually reversible in post-streptococcal disease of the CNS, permanent changes suggesting irreversible damage are well described.…”
Section: Studies Of Adultsmentioning
confidence: 99%
“…9,36,[48][49][50] Inflammatory changes have been described only occasionally in SC, and are usually localised to the basal ganglia (rarely with contrast enhancement). [51][52][53][54] In post-streptococcal dystonia and Parkinsonism, inflammatory changes involving the basal ganglia appear to be more common.…”
Section: Studies Of Adultsmentioning
confidence: 99%